Optimasi Strategi Penjualan Am2000 Tirtamart Dengan Algoritma Apriori Untuk Mengidentifikasi Produk Favorit Pelanggan - Bambang Sugito; Sri Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The retail industry faces increasing competition, and to survive, companies need to understand customer purchasing behavior and optimize their sales strategies. One effective approach is the use of data mining to analyze sales data and identify purchasing patterns. This study aims to optimize the sales strategy of Toko AM2000 by applying the Apriori algorithm to identify the most popular products among customers. The data used includes sales transactions from January to September 2024, with a total of 1,000 transactions and 10 attributes. The results of the analysis using the Apriori algorithm show a significant association between the products